Analysis of Factors Affecting the Event of High Pregnancy Mother in Blimbing Health Center Gudo Jombang District - Ati, Felomene Dian Sulistyananing; Nurdina; Suhita, Byba Melda (Journal for Research in Public Health, 2020)
A high risk pregnant woman still becomes a health issue/problem in the society. There are many factors who influence, such as the nutritious status, the anxiety, the health officers' role/workers' role and the ANC service. This research aims to indicate/detect the influence of the nutritious status, the anxiety, the health officers' role/workers' role and the ANC service to the high risk pregnant women. The research design is correlational analytic with the cross sectional approach. The total of the pregnant women with ANC service in Blimbing Gudo heaalth public clinic, Jombang district are 0ne hundred thirty four pregnant women per month with 150 respondents for sample by using simple random sampling methode. The free variable of the nutritious status, the anxiety, the health officers' role/workers' role and the ANC service and the correlation of the high risk pregnant women are collected with the questioners and analyzed by the double logistic regression. It is indicated that there is a connection/relation between the nutritious status and the high risk pregnant women (p 0.031<0.05), between the anxiety and the high risk pregnant women (p 0.003<0.05 ), between the the health public clinic officers' role and the high risk pregnant women (p 0.007<0.05 ), between the ANC service and the high risk pregnant women (p 0,001<0,05 ), there is an influence/impact simultaneously from the nutritious status, the anxiety, the health officers' role/workers' role and the ANC service to the high risk pregnant women' incident (p 0.011<0.05 ), and the most dominant/influential factor is the role of the health public clinic factors with B 4,778. It is caused by the midwife's practice which is the first chain/link of the pregnant women's health service. It is concluded that the nutritious status, the anxiety, the health officers' role/workers' role and the ANC service become predispotition of the high risk pregnant women